Myocardial work impairment in children with Wolff-Parkinson-White syndrome. (3rd October 2022) - Borrelli, N; Di Salvo, G; Ciriello, G D; Sabatino, J; Grimaldi, N; Barracano, R; Fusco, F; Merola, A; Correra, A; Romeo, E; Colonna, D; Palma, M; et al.
Abstract: Background: Wolf-Parkinson-White Syndrome (WPW) has been associated with reduced local myocardium deformation during systole. According to guidelines, when the left ventricle (LV) dysfunction is present catheter ablation of the accessory pathway may be required, even in asymptomatic patients. Purpose: The study aimed to assess the diagnostic value of non-invasive myocardial work in predicting subtle myocardial abnormalities in children with WPW. Methods: Eighty pediatric patients (age 7.91±3.2 years) were included in the study: 20 cases with manifest WPW and 60 age- and sex-matched controls (CTR). Global myocardial work index (MWI) was measured as the area of the LV pressure-strain loops. From MWI, global Constructive Work (MCW), Wasted Work (MWW) and Work Efficiency (MWE) were estimated. In addition, standard echocardiographic parameters of LV function were evaluated. Results: Patients characteristics are summarized in the table. Despite normal LV EF and GLS, children with WPW had worse MWI (WPW 1292.90±307.67 mmHg% vs CTR 1658.73±241.74 mmHg%, p=0.0000005), MCW (WPW 1844.15±267.96 mmHg% vs CTR 2104.90±237.85 mmHg%, p=0.00009), MWW (WPW 101.5 [85–148.25] mmHg% vs CTR 72 [54.75–109.25] mmHg%, p=0.004) and GWE (WPW 94 [91.75–95] mmHg% vs 96 [95–97] mmHg%, p=0.00012) (table). In the WPW group, MWE (r=−0.6, p=0.009) and MWW (r=0.6, p=0.01) was found to correlate with a prolonged QRS (figure). A multiple regression model was generated to identify the relation between abnormal myocardial work indices (worst interquartile range as dependent variable) and several independent variables. QRS was the best independent predictor of impaired myocardial work. In particular, a QRS>110 msec showed an 86% sensibility and 85% specificity for abnormal MWE (AUC of 0.85), and a 75% sensibility and 83% specificity for abnormal MWW (AUC of 0.83) (figure). Conclusion: In children with WPW, myocardial work indices were found significantly reduced, even in presence of normal LV EF and GLS. Prolonged QRS independently predicted myocardial impairment. In pediatric patients with WPW, myocardial work may represent a sensitive measure of LV dysfunction and help in the decision-making. Funding Acknowledgement: Type of funding sources: None.